Abscisic acid enhances SmAPK1-mediated phosphorylation of SmbZIP4 to positively regulate tanshinone biosynthesis in Salvia miltiorrhiza - Zhu, Ruiyan (The New phytologist, 2024)
© 2024 The Author(s). New Phytologist © 2024 New Phytologist Foundation.